The beautiful and damned and other stories - Fitzgerald, F. Scott (Francis Scott). (New York : Collins Classics, 2013)
The Beautiful and Damned, F. Scott Fitzgerald's second novel, tells the story of Anthony Patch, a 1920s socialite and presumptive heir to a tycoon's fortune, the relationship with his wife Gloria, his service in the army, and alcoholism. Anthony and Gloria are young and gorgeous, rich and leisured and they dedicate their lives to the pursuit of happiness and we follow the intimate story of their marriage as it disintegrates under the weight of their expectations, fueled by dissipation, jealousy and aimlessness. Fitzgerald skillfully portrays the Eastern elite as the Jazz Age begins its ascent, engulfing all classes into what will soon be known as Café Society. As with all of his other novels, it is a brilliant character study and is also an early account of the complexities of marriage and intimacy, largely based on Fitzgerald's relationship and marriage with Zelda Fitzgerald.
Keywords: AVARICE -- SOCIAL CONDITIONS -- FICTION